Improving the Image of Private Islamic Religious Colleges in the Kopertais Region XIII Jambi Through Public Relations Management - Aprianto, Iwan; Muntholib, Muntholib; Risnita, Risnita (International Journal of Educational Review, 2021)
The purpose of this research is to uncover and describe how public relations management might help improve the image of private Islamic religious universities in Kopertais area XIII Jambi. Through participant observation, this study employs a qualitative descriptive technique. The subjects of the study included the Head of the Private Islamic Religious College, Deputy Chair III for Student Affairs and Quality Assurance, and the administrative / staff section of the private Islamic religious college in Kopertais Region XIII Jambi. Observation, interviews, and documentation are all used to acquire data. Data analysis using the Miles and Huberman approach, which includes data reduction, data display, and verification or conclusion drawing. Focused on data analysis, it is possible to determine that public relations management improves image by executing management functions, which are then carried out by various programs that are conducted and based on establishing values of trust, motivation, or public perception, as well as higher education program activities aimed at the target. the general population, as well as the special society.